2018
DOI: 10.1007/s00018-017-2734-3
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid signaling and neurogenic niche regulation in the developing peripheral nervous system of the cephalochordate amphioxus

Abstract: The retinoic acid (RA) signaling pathway regulates axial patterning and neurogenesis in the developing central nervous system (CNS) of chordates, but little is known about its roles during peripheral nervous system (PNS) formation and about how these roles might have evolved. This study assesses the requirement of RA signaling for establishing a functional PNS in the cephalochordate amphioxus, the best available stand-in for the ancestral chordate condition. Pharmacological manipulation of RA signaling levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 109 publications
1
25
0
Order By: Relevance
“…Given the role of RA signaling in patterning the amphioxus general ectoderm (Schubert et al, 2004) and the scattered expression of CYP26-2 in this tissue (Carvalho et al, 2017), we next assessed the effects of CYP26 inhibition in the general ectoderm by assessing expression of Pax6, Tlx as well as Prdm12. The expression profiles of Pax6 and Tlx have previously been described during B. floridae development (Glardon et al, 1998;Kaltenbach et al, 2009;Lu et al, 2012) and those of Tlx have been reported in developing B. lanceolatum (Zieger, 2016). Furthermore, the effects of RA and BMS493 on Tlx expression have been assessed in B. lanceolatum (Zieger, 2016).…”
Section: Cyp26 Plays a Major Role In Patterning Specific Ectodermal Smentioning
confidence: 89%
See 2 more Smart Citations
“…Given the role of RA signaling in patterning the amphioxus general ectoderm (Schubert et al, 2004) and the scattered expression of CYP26-2 in this tissue (Carvalho et al, 2017), we next assessed the effects of CYP26 inhibition in the general ectoderm by assessing expression of Pax6, Tlx as well as Prdm12. The expression profiles of Pax6 and Tlx have previously been described during B. floridae development (Glardon et al, 1998;Kaltenbach et al, 2009;Lu et al, 2012) and those of Tlx have been reported in developing B. lanceolatum (Zieger, 2016). Furthermore, the effects of RA and BMS493 on Tlx expression have been assessed in B. lanceolatum (Zieger, 2016).…”
Section: Cyp26 Plays a Major Role In Patterning Specific Ectodermal Smentioning
confidence: 89%
“…The expression profiles of Pax6 and Tlx have previously been described during B. floridae development (Glardon et al, 1998;Kaltenbach et al, 2009;Lu et al, 2012) and those of Tlx have been reported in developing B. lanceolatum (Zieger, 2016). Furthermore, the effects of RA and BMS493 on Tlx expression have been assessed in B. lanceolatum (Zieger, 2016).…”
Section: Cyp26 Plays a Major Role In Patterning Specific Ectodermal Smentioning
confidence: 89%
See 1 more Smart Citation
“…(c) The early neurula (cross‐section view) and very early larva (lateral view) of amphioxus are shown. ESN s are (light blue) originated from the ventral ectoderm (Zieger et al., ). The arrows show the delamination and dorsal migration of ESN precursors (Kaltenbach et al., ).…”
Section: Pns Neurons Derived From Primitive Neural Crest and Placode mentioning
confidence: 99%
“…Nuclear DNA staining was performed for 10 minutes at room temperature using lanceolatum embryos and larvae were fixed overnight at 4ºC in freshly prepared ice-cold 4% paraformaldehyde in MOPS buffer [69]. Immunohistochemistry was performed as previously described [70], using a primary antibody against aPKC subsequently carried out with a mrf1-specific antisense riboprobe as previously described [69,71].…”
Section: Fluorescent Staining Immunohistochemistry and In Situ Hybrimentioning
confidence: 99%